IMPACTS OF THE SUSTAINABLE SOLAR MARKET GARDEN ON NATURAL RESOURCES EXPLOITATION, SOCIAL NETWORK, AND WOMEN’S INCOME IN UPPER NIGER, GUINEA - Bétéo Zongo; Abdouramane Djibo Gado; Bhèlè Lamah; Patrice Toé; Thomas Dogot (Socio-Economics/Agribusiness Department, 2023)
Climate adaptation and human pressure on natural resources are challenges for safeguarding and preserving the ecosystem and biodiversity in Upper Niger and particularly the Milo River basin. During the dry season, women’s sources of income are the exploitation of natural resources and rural exodus. The Solar Market Garden (SMG) is a way of climate adaptation by employing women to reduce human pressure on natural resources and improve their socio-economic conditions. The overall aim is to assess the environmental and socioeconomic profitability of solar irrigation practicing garden market in Banankoni village along Milo River in Upper Niger, Guinea. Data collection includes investment in solar-powered irrigation systems, demographic characteristics of women, inputs for crops, selling prices of vegetables, and the impacts of SMG. Environmental and social impacts of SMG were analyzed by comparing women’s practices before and during garden market perimeter valorization. Assessment of the Internal Rate of Return (IRR), Payback Period (PBP), and Benefit-Cost Ratio (BCR) was used to analyze the economic impacts of SMG. SMG stimulates social cohesion and improves women’s position in households. It is an alternative to rural exodus and deforestation by creating employment. SMG practice enhances food security diversity, nutritious value, and the microenvironment through the consumption of produced vegetables. The NPV, IRR, and PBP analysis showed that SMG is economically profitable for women in Banankoni village during dry seasons. Most women (92.4%) are willing to invest to scale up SMG which is a pathway to decrease human pressure on natural resources and improve food security, the social status of women, and their income in the climate change context.